Improvement of Reliability and Power Quality using Battery Energy Storage System of Distribution Network - Mukul S Soman,; Prof. Vishal Mehtre,; Prof. S.A. Namekar, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The integration of renewable electricity sources (RES) into electricity grids poses sizable demanding situations to electricity high-satisfactory and reliability because of their intermittent and unpredictable nature. Battery Energy Storage Systems (BESS) gift a feasible strategy to mitigate those demanding situations. This paper explores the function of BESS in enhancing electricity high-satisfactory and reliability in distribution systems. Failure to supply a top-notch electric provider to commercial and home clients can cause huge financial losses and human inconvenience. A strategy to this hassle may be development of flatness and length of the voltage curve. Energy Storage Systems (ESS) may be hired to enhance the reliability and high-satisfactory of electricity deliver at selective load furnished with the aid of using lengthy radial networks. This observe affords a load waft simulation-primarily based totally technique for assessing the reliability and electricity high-satisfactory development capability of a distribution community the usage of an Energy Storage System. The proposed method may be used to set up the right sizing and garage potential to reap a given objective. The paper examines a case observe for a Mumbai Distribution Network and establishes the connection among the anticipated values of reliability indices and the electricity garage length. The outcomes of the simulation reveal the development of reliability and electricity high-satisfactory of deliver with the addition of an ESS placed on the far-off substation. However, consistent with ESS value information posted in literature, the proposed alternative might also additionally nonetheless be varied.
Keywords: BESS; Power Quality; Reliability; SAIFI; SAIDI; CAIDI